Humerus Fracture Healing Using Traditional Chinese Medicine - Fadlul Azim Fauzi Mansur; Siti Soraya Ab Rahman; Mohd Asha'ari Bain; Zetty Nadia Mohd Zain; Mohd Shaffid Md. Shariff (USIM Press, 2024)
Vol. 7 No. 3 (2021): Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience (Case Report)